Kuratela penitencjarna jako element strategii przeciwdziałania wtórnej przestępczości - Jasiński, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Probation officers carry out tasks, defined by law, relating to education, resocialisation, diagnostics, prevention and control among offenders, also in penal institutions Act of 27 July 2001 on Probation Officers, Journal of Laws 2001 No. 98 item 1071, Article 1. In penal institutions probation officers co-develop and then implement the so-called “freedom plans”. These are sets of actions, preceded by a diagnosis of needs and deficits, which are derived from the possibilities and potential of offenders as well as shortcomings needed to be overcome in order to achieve the minimum objective — prevention of reoffending.
Keywords: kuratela; readaptacja społeczna; jednostki penitencjarne; organizacje pozarządowe